Cardiac Magnetic Resonance in myocarditis: besides the diagnosis?. (3rd May 2023) - Rocha Carvalho, P; Carvalho, C; Bernardo, M; Moreira, I; Silveira, I; Ferreira, C; Fontes, P; Moreira, J I
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Patients with acute myocarditis (AM) can be at increased risk of adverse cardiac events after the index episode. Beyond its undoubted role in diagnosis, Cardiac Magnetic Resonance (CMR) can also provide additional prognostic information and contribute to the patients risk stratification. Methods: Retrospective study with patients admitted with the clinical suspicion of myocarditis in our center from February/2018 to September/2021, in whom CMR was performed. A total of 48 patients were included and divided into two groups based on the number of segments with late gadolinium enhancement (LGE). The threshold (> or < than 5 segments) was determined according to ROC curve analysis. The primary outcome was a composite of all-cause mortality, heart failure and myocarditis recurrence. Results: We included 48 patients (95, 8% males; mean age 37, 0±16, 1 years old), 93, 8% presenting with chest pain and 63, 2% presenting with st-segment elevation on electrocardiogram. During hospitalization, 3 patients needed ionotropic support, 7 had supraventricular tachycardia, 9 non-sustained ventricular tachycardia, 1 sustained ventricular tachycardia, 1 needed extracorporeal membrane oxygenation and 9 had heart failure. CMR (performed 6 days (median) after admission) showed LGE in 45 patients (93, 8%) and mean left ventricular ejection fraction (LVEF) of 55, 5±8, 7%. Both groups had similar age (35, 0±13, 7 vs 38, 5±17, 6 years, p=0, 45), cardiovascular risk factors, st-segment elevation at admission (61, 9% vs 63, 0%, p=0, 38), pro-BNP levels at admission [286 (IQR 144-699) mg/dl vs 522 (IQR 222-1253) mg/dl, p = 0, 20] and peak C-reactive protein [5, 7 (IQR 4-12) vs 5, 2 (IQR 2, 6-12, 5), p=0, 77]. Patients with LGE in ≥5 segments (56, 3%) had lower LVEF (53, 2±9, 6 vs 58, 2±6, 6, p=0, 02), had more non-sustained ventricular tachycardia episodes (29, 6% vs 4, 8%, p=0, 03), incidence of heart failure during hospitalization (25, 9% VS 9, 6%, p=0, 19) and higher peak troponin levels [1, 54 (IQR0, 64-2, 45) vs 0, 594 (IQR 0, 374-1, 07), p=0, 002]. During a median follow-up of 21, 5 (IQR 8–35, 2) months, 11 patients (22, 9%) experienced the primary outcome (6 for heart failure, 4 for AM recurrence, 1 death). The incidence of the primary endpoint increased by 1, 20 (95% CI 1, 08-1, 60) for each segment involved. Patients with ≥ 5 segments had a higher incidence of this outcome (25, 7 vs 5, 1 per 100 patient/year, log rank p=0, 02). After adjusting for possible cofounders, LGE≥ 5 segments on CMR was an independent predictor of all-cause mortality, heart failure and myocarditis recurrence (HR 7, 22, 95% CI 1, 33-39, 16). Conclusion: In this study, LGE involving 5 or more segments by LGE was correlated with adverse cardiovascular events among patients with suspected myocarditis. These data suggest that cardiac resonance imaging might add value to currently existing diagnostic tools for risks assessment in AM.